Solid Variant of Adenoid Cystic Carcinoma: Difficulties in Diagnostic Recognition. (August 2016) - Ben Salha, Imen; Bhide, Shree; Mourtzoukou, Despoina; Fisher, Cyril; Thway, Khin
Adenoid cystic carcinoma (ACC) is a malignant neoplasm that mainly affects the salivary glands but has been described in many other anatomical sites. It is composed of basaloid cells with myoepithelial/basal cell differentiation and ductal epithelial cells that proliferate in a fibrous stroma, with variable amounts of myxohyaline material. Three patterns (cribriform, tubular, and solid) occur, and the solid variant is characterized by a predominant compact sheet-like and nested pattern of rounded basaloid cells lacking obvious cribriform or tubular architecture. The solid variant has significant morphological and immunohistochemical overlap with a large range of neoplasms of different lineages, including other carcinomas and sarcomas. We describe a case of solid variant ACC of the paranasal sinuses, which showed an almost entirely solid pattern of growth (in >95% of cells) and which on initial biopsy showed no features of classical ACC. This highlights the potential for diagnostic misinterpretation with a variety of other neoplasms, which is particularly important because of the significant difference in treatment for ACC and tumors in its differential diagnosis.